Properties of bituminous mix and binder modified with waste polyethylene terephthalate / Zahra Kalantar - Zahra, Kalantar (2012)
Waste materials can be recycled to produce valuable construction materials for pavements. Many different types of waste materials have been and are currently being used in this application. The challenge is to recognize potential uses of the various waste materials and to apply engineering solutions for their use in pavement construction. Using PET-modified (Polyethylene Terephthalate) binders also contribute to the recirculation of plastic waste, as well as to the protection of the environment. The purpose of this research is to investigate the possibility of using waste material in road construction and also to study the effect of waste polyethylene terephthalate on the rheological properties of the binder. The research methodology involves a series of tests, which are separated into two parts: - The first part is binder tests on bitumen modified with PET - The second part is IDT (Indirect Tensile) and Marshall test on PET modified bituminous mixes A statistical analysis was also done to compare the results and present the significant differences between results. The results showed that the decreased penetration and increased softening point temperature increased the stiffness (hardness) of the PMBs (polymers modified bitumen). The results demonstrate that the asphalt mixtures prepared with the PET (Polyethylene Terephthalate) may be less sensitive to permanent deformation. Along with the parameters related to penetration and softening point test the increased viscosity values and indices also indicated the stiffening effect of PET modification. It may also be inferred that PET-modified bituminous binders provide better resistance against permanent deformations due to their higher complex shear modulus and lower phase angle as compared to conventional binder. The results of the Marshall test indicated that the modified mixture have a higher stability compared to non-modified mixtures. This would positively influence the rutting resistance of these mixtures. The air void contents of the modified mixture decreases with increasing binder content. VIM (Void in Air) in all binder contents decreases as the amount of PET used increases. Air void proportion around 4% is enough to provide room for the expansion of asphalt binder to prevent bleeding or flushing that would reduce the skid resistance of the pavement and increase fatigue resistance susceptibility.